Effect of Fiber and Fecal Microbiota Transplantation Donor on Recipient Mice Gut Microbiota - Zhong, Yifan; Cao, Jiahong; Deng, Zhaoxi; Ma, Yanfei; Liu, Jianxin; Wang, Haifeng (Frontiers in Microbiology, 2021)
Both fecal microbiota transplantation (FMT) and dietary fiber intervention were verified as effective ways to manipulate the gut microbiota, while little is known about the influence of the combined methods on gut microbiota. Here, we constructed “non-industrialized” and “industrialized” gut microbiota models to investigate the donor effect of FMT and diet effect in shaping gut microbiota. Mice were transplanted fecal microbiota from domestic pig and received a diet with low-fiber (D) or high-fiber (DF), while the other two groups were transplanted fecal microbiota from wild pig and then received a diet with low-fiber (W) or high-fiber (WF), respectively. Gut microbiota of WF mice showed a lower Shannon and Simpson index (P < 0.05), while gut microbiota of W mice showed no significant difference than that of D and DF mice. Random forest models revealed the major differential bacteria genera between four groups including Anaeroplasma or unclassified_o_Desulfovibrionales, were influenced by FMT or diet intervention, respectively. Besides, we found a lower out-of-bag (OOB) rate in the random forest model constructed for dietary fiber (0.086) than that for FMT (0.114). LDA effective size (LEfSe) demonstrated that FMT combined with dietary fiber altered specific gut microbiota, including Alistipes, Clostridium XIVa, Clostridium XI, and Akkermansia, in D, DF, W, and WF mice, respectively. Our results revealed that FMT from different donors coupled with dietary fiber intervention could lead to different patterns of gut microbiota composition, and dietary fiber might play a more critical role in shaping gut microbiota than FMT donor. Strategies based on dietary fiber can influence the effectiveness of FMT in the recipient.